Monitoring as a Pedagogical Definition - Olena Kukharuk (Pedagogical Discourse, 2014)
The article deals with the problem of interpretation of the term «monitoring» in different sources of scientific information. Conducted thorough research of the main approaches to defining the essence of the concept of «monitoring» by analyzing the psychological and educational literature, reference and encyclopedias. Materials research that had the greatest impact on the interpretation of the term «monitoring» contained in the text. An analysis of the sources of information were singled out key concepts and statements that serve the general components of the monitoring process. Based on the data performed a comprehensive and obiective analysis of the concept of «monitoring» as a pedagogical definitions and clarified its meaning. It is concluded that monitoring serves as a comprehensive system, the effective work of which depends on the constant and timely implementation of necessary measures. Established that such measures must be organization, collection, processing, classification, analysis, synthesis, evaluation, interpretation and dissemination of information.